1995
DOI: 10.1128/aac.39.3.680
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and ex vivo activities of antimicrobial agents used in combination with clarithromycin, with or without amikacin, against Mycobacterium avium

Abstract: MICs of clarithromycin, amikacin, isoniazid, rifabutin, ciprofloxacin, sparfloxacin, ethambutol, and clofazimine were determined for six isolates of Mycobacterium avium complex (MAC) from AIDS patients both by the radiometric method and by an ex vivo model of infection in human macrophages. The median MICs in macrophages were similar or slightly lower than values found in broth, except for amikacin, which had slightly higher MICs inside the cells. Combinations of clarithromycin with other antimicrobial agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Only AMK had a substantial effect by improving the activity of the combination CLR-EMB tenfold within only 3 days of exposure. This is in agreement with the findings of Fattorini et al, demonstrating that the addition of AK made the combination of CLR-EMB synergistic against a number of MAC strains in vitro (17).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Only AMK had a substantial effect by improving the activity of the combination CLR-EMB tenfold within only 3 days of exposure. This is in agreement with the findings of Fattorini et al, demonstrating that the addition of AK made the combination of CLR-EMB synergistic against a number of MAC strains in vitro (17).…”
Section: Discussionsupporting
confidence: 83%
“…Aminoglycosides have been used in clinical studies in successful treatment regimens, whereas other investigators failed to show a beneficial effect of aminoglycosides (36). However, Fattorini et al demonstrated in in vitro assays that AMK significantly improved the activity of the CLR-EMB combination (17). The potential risks and benefits of treatment with aminoglycosides should be weighed carefully.…”
Section: Discussionmentioning
confidence: 99%
“…The combination clarithromycin-clofazimine also showed synergy against MAC strains in checkerboard evaluation (7). These checkerboard titrations offer no information on the mechanism of synergistic activity, the exact killing activity of these combinations, or its concentration dependence.…”
mentioning
confidence: 99%
“…Leukocyte buffy coats obtained from healthy donors were separated over Ficoll-Hypaque (Histopaque 1077 ; Sigma), as previously described (Fattorini et al, 1995). Briefly, suspensions of isolated peripheral blood mononuclear cells prepared in complete RPMI 1640 medium (Life Technologies) containing 10 % heat-inactivated (56 mC, 30 min) fetal calf serum, 25 mM HEPES and 2 mM -glutamine were adjusted to 1i10( cells ml − " and distributed in 0n5 ml volumes in 24-well tissue culture plates.…”
Section: Micro-organism and Isolation Of Colonial Variantsmentioning
confidence: 99%
“…Cell viability was determined by the trypan blue exclusion method. At various times, infected macrophages were lysed to determine the number of c.f.u., as previously described (Fattorini et al, 1995).…”
Section: Micro-organism and Isolation Of Colonial Variantsmentioning
confidence: 99%